EXAFS and EPR analysis of the local structure of Mn‐doped Li2B4O7. Issue 7 (30th January 2013) - Kelly, T. D.; Kong, L.; Buchanan, D. A.; Brant, A. T.; Petrosky, J. C.; McClory, J. W.; Adamiv, V. T.; Burak, Y. V.; Dowben, P. A.
Abstract The local structure of Mn‐doped Li2B4O7(001) was investigated using extended X‐ray absorption fine structure (EXAFS) at the Mn K edge and electron paramagnetic resonance (EPR). The location of the Mn dopant in a lithium tetraborate crystal is consistent with occupation of a site with strong oxygen coordination. The MnO bond lengths are similar to those observed with Mn doping of the icosahedral based boron carbide where Mn is in a substitutional dopant in one of the cage sites. From EXAFS, the manganese does not appear to greatly alter the overall tetragonal form of lithium tetraborate, with the dopant most likely substituting for one of the two B sites and with placement of some of the Mn in a Li site still possible. The EPR spectra agree with the literature examined resolving multiple Mn species in the crystal lattice.